DETERMINAN KINERJA PELAKU IKM BATIK DI KOTA DENPASAR PROVINSI BALI - I Nyoman Wahyu Widiana (WORLDVIEW ( Development economic and sharia studies journal ), 2023)
The purpose of this study was to determine the influence of internal and external factors on the performance of IKM Batik actors in Denpasar City. The sample in this study was the perpetrators of IKM Batik in Denpasar City as many as 57 people. Sources of data used are primary and secondary data. Data analysis using SPSS for Windows version 21. The data collection procedure in this study used observation techniques, documentation studies, and questionnaires using a Likert scale. The data analysis technique used multiple linear regression analysis.The results obtained from statistical analysis show that there is a positive and significant influence between internal factors on the performance of KM Batik in Denpasar City, seen from the t-test results, it is obtained that t1-count is 4.175 greater than t-table of 1.671 and sig value of 0.000. There is a positive and significant influence between external factors on the performance of IKM Batik in Denpasar City, seen from the results of the t-test, the t2-count is 6.099 which is greater than the t-table of 1.671 and the sig value is 0.000. There is a positive and significant influence between internal and external factors on the performance of IKM Batik in Denpasar City, the F-count is 91.336 which is greater than the F-table of 3.11